{"title":"Lidstone interpolation III. Several variables","authors":"M. Waldschmidt","doi":"10.1090/btran/135","DOIUrl":null,"url":null,"abstract":"<p>A polynomial in a single variable is uniquely determined by its derivatives of even order at 0 and 1. More precisely, such an univariate polynomial can be written and a finite sum of <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"f Superscript left-parenthesis 2 n right-parenthesis Baseline left-parenthesis 0 right-parenthesis normal upper Lamda Subscript n Baseline left-parenthesis 1 minus z right-parenthesis\">\n <mml:semantics>\n <mml:mrow>\n <mml:msup>\n <mml:mi>f</mml:mi>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>2</mml:mn>\n <mml:mi>n</mml:mi>\n <mml:mo stretchy=\"false\">)</mml:mo>\n </mml:mrow>\n </mml:msup>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>0</mml:mn>\n <mml:mo stretchy=\"false\">)</mml:mo>\n <mml:msub>\n <mml:mi mathvariant=\"normal\">Λ<!-- Λ --></mml:mi>\n <mml:mi>n</mml:mi>\n </mml:msub>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>1</mml:mn>\n <mml:mo>−<!-- − --></mml:mo>\n <mml:mi>z</mml:mi>\n <mml:mo stretchy=\"false\">)</mml:mo>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">f^{(2n)}(0) \\Lambda _n(1-z)</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> and <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"f Superscript left-parenthesis 2 n right-parenthesis Baseline left-parenthesis 1 right-parenthesis normal upper Lamda Subscript n Baseline left-parenthesis z right-parenthesis\">\n <mml:semantics>\n <mml:mrow>\n <mml:msup>\n <mml:mi>f</mml:mi>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>2</mml:mn>\n <mml:mi>n</mml:mi>\n <mml:mo stretchy=\"false\">)</mml:mo>\n </mml:mrow>\n </mml:msup>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>1</mml:mn>\n <mml:mo stretchy=\"false\">)</mml:mo>\n <mml:msub>\n <mml:mi mathvariant=\"normal\">Λ<!-- Λ --></mml:mi>\n <mml:mi>n</mml:mi>\n </mml:msub>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mi>z</mml:mi>\n <mml:mo stretchy=\"false\">)</mml:mo>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">f^{(2n)}(1) \\Lambda _n(z)</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula>, (<inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"n greater-than-or-equal-to 0\">\n <mml:semantics>\n <mml:mrow>\n <mml:mi>n</mml:mi>\n <mml:mo>≥<!-- ≥ --></mml:mo>\n <mml:mn>0</mml:mn>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">n\\ge 0</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula>), where the <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"normal upper Lamda Subscript n Baseline left-parenthesis z right-parenthesis\">\n <mml:semantics>\n <mml:mrow>\n <mml:msub>\n <mml:mi mathvariant=\"normal\">Λ<!-- Λ --></mml:mi>\n <mml:mi>n</mml:mi>\n </mml:msub>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mi>z</mml:mi>\n <mml:mo stretchy=\"false\">)</mml:mo>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">\\Lambda _n(z)</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> are the Lidstone polynomials defined by the conditions <disp-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"left-parenthesis StartFraction normal d Over normal d z EndFraction right-parenthesis Superscript 2 k Baseline normal upper Lamda Subscript n Baseline left-parenthesis 0 right-parenthesis equals 0 and left-parenthesis StartFraction normal d Over normal d z EndFraction right-parenthesis Superscript 2 k Baseline normal upper Lamda Subscript n Baseline left-parenthesis 1 right-parenthesis equals delta Subscript k comma n Baseline comma k greater-than-or-equal-to 0 comma n greater-than-or-equal-to 0 period\">\n <mml:semantics>\n <mml:mrow>\n <mml:msup>\n <mml:mrow>\n <mml:mo>(</mml:mo>\n <mml:mfrac>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi mathvariant=\"normal\">d</mml:mi>\n </mml:mrow>\n <mml:mrow>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi mathvariant=\"normal\">d</mml:mi>\n </mml:mrow>\n <mml:mi>z</mml:mi>\n </mml:mrow>\n </mml:mfrac>\n <mml:mo>)</mml:mo>\n </mml:mrow>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mn>2</mml:mn>\n <mml:mi>k</mml:mi>\n </mml:mrow>\n </mml:msup>\n <mml:msub>\n <mml:mi mathvariant=\"normal\">Λ<!-- Λ --></mml:mi>\n <mml:mi>n</mml:mi>\n </mml:msub>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>0</mml:mn>\n <mml:mo stretchy=\"false\">)</mml:mo>\n <mml:mo>=</mml:mo>\n <mml:mn>0</mml:mn>\n <mml:mtext> and </mml:mtext>\n <mml:msup>\n <mml:mrow>\n <mml:mo>(</mml:mo>\n <mml:mfrac>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi mathvariant=\"normal\">d</mml:mi>\n </mml:mrow>\n <mml:mrow>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi mathvariant=\"normal\">d</mml:mi>\n </mml:mrow>\n <mml:mi>z</mml:mi>\n </mml:mrow>\n </mml:mfrac>\n <mml:mo>)</mml:mo>\n </mml:mrow>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mn>2</mml:mn>\n <mml:mi>k</mml:mi>\n </mml:mrow>\n </mml:msup>\n <mml:msub>\n <mml:mi mathvariant=\"normal\">Λ<!-- Λ --></mml:mi>\n <mml:mi>n</mml:mi>\n </mml:msub>\n <mml:mo stretchy=\"false\">(</mml:mo>\n <mml:mn>1</mml:mn>\n <mml:mo stretchy=\"false\">)</mml:mo>\n <mml:mo>=</mml:mo>\n <mml:msub>\n <mml:mi>δ<!-- δ --></mml:mi>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi>k</mml:mi>\n <mml:mo>,</mml:mo>\n <mml:mi>n</mml:mi>\n </mml:mrow>\n </mml:msub>\n <mml:mo>,</mml:mo>\n <mml:mspace width=\"1em\" />\n <mml:mi>k</mml:mi>\n <mml:mo>≥<!-- ≥ --></mml:mo>\n <mml:mn>0</mml:mn>\n <mml:mo>,</mml:mo>\n <mml:mspace width=\"thickmathspace\" />\n <mml:mi>n</mml:mi>\n <mml:mo>≥<!-- ≥ --></mml:mo>\n <mml:mn>0.</mml:mn>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">\\begin{equation*} \\left (\\frac {\\mathrm {d}}{\\mathrm {d}z}\\right )^{2k} \\Lambda _n(0)=0\\text { and } \\left (\\frac {\\mathrm {d}}{\\mathrm {d}z}\\right )^{2k} \\Lambda _n(1)=\\delta _{k,n},\\quad k\\ge 0, \\; n\\ge 0. \\end{equation*}</mml:annotation>\n </mml:semantics>\n</mml:math>\n</disp-formula>\n We generalize this theory to <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"n\">\n <mml:semantics>\n <mml:mi>n</mml:mi>\n <mml:annotation encoding=\"application/x-tex\">n</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> variables, replacing the two points <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"0\">\n <mml:semantics>\n <mml:mn>0</mml:mn>\n <mml:annotation encoding=\"application/x-tex\">0</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula>, <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"1\">\n <mml:semantics>\n <mml:mn>1</mml:mn>\n <mml:annotation encoding=\"application/x-tex\">1</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> in <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"double-struck upper C\">\n <mml:semantics>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:mi mathvariant=\"double-struck\">C</mml:mi>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">\\mathbb {C}</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> with <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"n plus 1\">\n <mml:semantics>\n <mml:mrow>\n <mml:mi>n</mml:mi>\n <mml:mo>+</mml:mo>\n <mml:mn>1</mml:mn>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">n+1</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> points <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"e underbar Subscript 0 Baseline comma e underbar Subscript 1 Baseline comma ellipsis comma e underbar Subscript n Baseline\">\n <mml:semantics>\n <mml:mrow>\n <mml:msub>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:munder>\n <mml:mi>e</mml:mi>\n <mml:mo>_<!-- _ --></mml:mo>\n </mml:munder>\n </mml:mrow>\n <mml:mn>0</mml:mn>\n </mml:msub>\n <mml:mo>,</mml:mo>\n <mml:msub>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:munder>\n <mml:mi>e</mml:mi>\n <mml:mo>_<!-- _ --></mml:mo>\n </mml:munder>\n </mml:mrow>\n <mml:mn>1</mml:mn>\n </mml:msub>\n <mml:mo>,</mml:mo>\n <mml:mo>…<!-- … --></mml:mo>\n <mml:mo>,</mml:mo>\n <mml:msub>\n <mml:mrow class=\"MJX-TeXAtom-ORD\">\n <mml:munder>\n <mml:mi>e</mml:mi>\n <mml:mo>_<!-- _ --></mml:mo>\n </mml:munder>\n </mml:mrow>\n <mml:mi>n</mml:mi>\n </mml:msub>\n </mml:mrow>\n <mml:annotation encoding=\"application/x-tex\">{\\underline {e}}_0,{\\underline {e}}_1,\\dots ,{\\underline {e}}_n</mml:annotation>\n </mml:semantics>\n</mml:math>\n</inline-formula> in <inline-formula content-type=\"math/mathml\">\n<mml:math xmlns:mml=\"http://www.w3.org/1998/Math/MathML\" alttext=\"double-struck upper C Superscript n\">\n <mml:semantics>\n <mml:msup","PeriodicalId":377306,"journal":{"name":"Transactions of the American Mathematical Society, Series B","volume":"52 ","pages":"0"},"PeriodicalIF":0.0000,"publicationDate":"2023-02-06","publicationTypes":"Journal Article","fieldsOfStudy":null,"isOpenAccess":false,"openAccessPdf":"","citationCount":"0","resultStr":null,"platform":"Semanticscholar","paperid":null,"PeriodicalName":"Transactions of the American Mathematical Society, Series B","FirstCategoryId":"1085","ListUrlMain":"https://doi.org/10.1090/btran/135","RegionNum":0,"RegionCategory":null,"ArticlePicture":[],"TitleCN":null,"AbstractTextCN":null,"PMCID":null,"EPubDate":"","PubModel":"","JCR":"","JCRName":"","Score":null,"Total":0}
引用次数: 0
Abstract
A polynomial in a single variable is uniquely determined by its derivatives of even order at 0 and 1. More precisely, such an univariate polynomial can be written and a finite sum of f(2n)(0)Λn(1−z)f^{(2n)}(0) \Lambda _n(1-z) and f(2n)(1)Λn(z)f^{(2n)}(1) \Lambda _n(z), (n≥0n\ge 0), where the Λn(z)\Lambda _n(z) are the Lidstone polynomials defined by the conditions (ddz)2kΛn(0)=0 and (ddz)2kΛn(1)=δk,n,k≥0,n≥0.\begin{equation*} \left (\frac {\mathrm {d}}{\mathrm {d}z}\right )^{2k} \Lambda _n(0)=0\text { and } \left (\frac {\mathrm {d}}{\mathrm {d}z}\right )^{2k} \Lambda _n(1)=\delta _{k,n},\quad k\ge 0, \; n\ge 0. \end{equation*}
We generalize this theory to nn variables, replacing the two points 00, 11 in C\mathbb {C} with n+1n+1 points e_0,e_1,…,e_n{\underline {e}}_0,{\underline {e}}_1,\dots ,{\underline {e}}_n in